Virtual 2D angiography from four-dimensional digital subtraction angiography (4D-DSA): A feasibility study. Issue 2 (April 2021) - Yu, Jay F; Pung, Leland; Minami, Hataka; Mueller, Kerstin; Khangura, Rajkamal; Darflinger, Robert; Hetts, Steven W; Cooke, Daniel L
Background: Digital subtraction angiography (DSA) remains the gold standard for angiographic evaluation of cerebrovascular pathology, however, multiple acquisitions requiring additional time and radiation are often needed. In contrast, 3D-DSA provides volumetric information from a single injection but neglects temporal information. Four-dimensional-DSA (4D-DSA) combines temporal information of 2D-DSA with volumetric information of 3D-DSA to provide time-resolved tomographic 3D reconstructions, potentially reducing procedure time and radiation. This work evaluates the diagnostic quality of virtual single-frame 4D-DSA relative to 2D-DSA images by assessing clinicians' ability to evaluate cerebrovascular pathology. Methods: Single-frame images of four projections from 4D-DSA and their corresponding 2D-DSA images (n = 15) were rated by two neurointerventional radiologists. Images were graded based on diagnostic quality (0 = non-diagnostic, 1 = poor, 2 = acceptable, 3 = good). Dose area product (DAP) for each case was recorded for all 2D-DSA, 4D-DSA acquisitions, and the overall procedure. Results: The mean diagnostic quality of all four 4D-DSA projections from both raters was 1.75 while the mean of 2D-DSA projections was 2.8. Student's t-test revealed significant difference in diagnostic quality between 4D-DSA and 2D-DSA at all four projections (p < 0.001). On average 4D-DSA acquisitions accounted for 30% dose compared to the overall average aggregated dose per procedure. Conclusions: The difference in image quality between virtual single-frame 4D-DSA and their respective 2D-DSA images is statistically significant. Furthermore, 4D-DSA acquisitions require less radiation dose than conventional procedures with 2D-DSA acquisitions.